2012
DOI: 10.3382/ps.2011-01825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding hemp seed and hemp seed oil on laying hen performance and egg yolk fatty acid content: Evidence of their safety and efficacy for laying hen diets

Abstract: Forty-eight 19-wk-old Bovan White laying hens were fed 1 of 5 diets containing either hemp seed (HS) or hemp seed oil (HO). The level of HO was 4, 8, or 12%, whereas the level was 10 or 20% for the HS. A set of 8 birds fed wheat-, barley-, and corn oil-based diets served as the control. Performance was monitored over 12 wk. Average hen-day egg production was not affected upon feeding of either HS or HO diets. Egg weight was higher than that of the controls for hens consuming the 20% HS diet (P < 0.05). Feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 15 publications
10
63
0
Order By: Relevance
“…Contrary to the potential of industrial hempseed, its use in the poultry diet is not recommended due to a lack of scientific evidence to support nutritional efficacy (Gakhar et al, 2012). Previous reports have shown that the addition of hempseed can potentially generate n-3-enriched eggs (Silversides and Lefrançois, 2005;Gakhar et al, 2012;Neijat et al, 2015). In the present study, the results are encouraging since the profile of fatty acids improved significantly.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Contrary to the potential of industrial hempseed, its use in the poultry diet is not recommended due to a lack of scientific evidence to support nutritional efficacy (Gakhar et al, 2012). Previous reports have shown that the addition of hempseed can potentially generate n-3-enriched eggs (Silversides and Lefrançois, 2005;Gakhar et al, 2012;Neijat et al, 2015). In the present study, the results are encouraging since the profile of fatty acids improved significantly.…”
Section: Discussionsupporting
confidence: 76%
“…The fatty acid profile of egg yolk could be altered by adding natural sources of n-3 PUFA into the diet of the hen (Baucells et al, 2000). Contrary to the potential of industrial hempseed, its use in the poultry diet is not recommended due to a lack of scientific evidence to support nutritional efficacy (Gakhar et al, 2012). Previous reports have shown that the addition of hempseed can potentially generate n-3-enriched eggs (Silversides and Lefrançois, 2005;Gakhar et al, 2012;Neijat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19-), and elongases (ELOVL2; EC 2.3.1.199-and ELOVL5; EC 2.3.1.199-). [38][39][40][41][42] In hyperglycemic humans and chick embryos, desaturases act on multiple substrates but prefer n-3 fatty acid substrates as compared to n-6 fatty acids. 36,43 As medium NAC-and/or EtOH and medium NAC-induced peroxidation initially attacked DHA (22:6, n-3), coupled with the virtual nonexistence of α-linolenic acid (18:3, n-3) (Table 1), Δ 5 -and Δ 6 -desaturases perhaps began the elongation and desaturation of linoleic acid (18:2, n-6) and γ-linolenic (18:3, n-6) causing increased arachidonic acid (20:4, n-6) and DPA (22:5, n-6).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy rests on the ability of laying hens to convert ALA to DHA. Some researchers reported that the n-3 fatty acid level of eggs increased by adding plant sources of n-3 PUFA (ALA), such as flax seed (Hayat et al, 2009), hemp seed (Gakhar et al, 2012) or chia seed (Ayerza, 2009). For example, the inclusion of 10% flaxseed (~33% ALA) in the diets of laying hens resulted in a higher accumulation of n-3 fatty acids than a control diet (Bean and Leeson, 2003).…”
Section: Introductionmentioning
confidence: 99%